Interiorização da UFG na regional Catalão : reflexões sobre as condições de trabalho do docente - Silva, Maria José da (2017)
In this research, we aimed to investigate the working conditions of UFG teachers in the Regional Catalão, in the process of expansion and internalization of federal universities, from 2006 to 2014. The theoretical studies in the works of João dos Reis Silva Júnior and Valdemar Sguissardi - “Novas faces da educação superior no Brasil: reforma do Estado e mudança na produção”; Valdemar Sguissardi and João dos Reis Silva Júnior - “O trabalho intensificado nas federais: pós-graduação e produtivismo acadêmico” - were fundamental in the systematic development of this research. The work is structured in three chapters: the first, the context of the federal universities expansion and UFG Regional Catalão expansion process; the second, on the process of UFG expansion and internalization and the third, the analysis of the teachers interviews regarding the working conditions of UFG teachers in Regional Catalão. The methodology used was written and oral sources, in these, we interviewed teachers who were already part of the institution and those who entered from the expansion programs (Phase I and REUNI). We conclude that UFG teachers in Regional Catalão, due to the difficulties found in the working conditions, accumulated for themselves a working overload.